The Influence of Environment, Workload, Financial and Non-Financial Compensation on Work Motivation at DPMPTSP Makassar - Nurlina Nurlina; Edy Jumady (Universitas Dharma Wacana, 2022)
This study examines the effect of the environment, workload, financial and non-financial compensation on employee motivation at DPMPTSP Makassar City. The research questions posed in this study are: does the work environment affect work motivation, whether workload affects work motivation, and whether compensation has an effect on employee motivation. This research was conducted at DPMPTSP Makassar City. There are 52 respondents who have been selected as samples using the saturated sampling technique. The method of data collection is by using a questionnaire. The data analysis technique in this research is multiple linear regression analysis. The study found that the hypothesis in this study has been significantly proven. The work environment has a positive and significant effect on work motivation, workload has a negative and insignificant effect on work motivation, and compensation has a positive and significant effect on employee motivation. The implication of this research is that the work environment and compensation have an equally important role in increasing employee motivation at DPMPTSP Makassar City